2018
DOI: 10.1063/1.5019592
|View full text |Cite
|
Sign up to set email alerts
|

Preserved cardiac function by vinculin enhances glucose oxidation and extends health- and life-span

Abstract: Despite limited regenerative capacity as we age, cardiomyocytes maintain their function in part through compensatory mechanisms, e.g., Vinculin reinforcement of intercalated discs in aged organisms. This mechanism, which is conserved from flies to non-human primates, creates a more crystalline sarcomere lattice that extends lifespan, but systemic connections between the cardiac sarcomere structure and lifespan extension are not apparent. Using the rapidly aging fly system, we found that cardiac-specific Vincul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…It was reported that increased Vinculin (Vinc) expression in Drosophila cardiac muscle cells improves cardiac function and extends lifespan (Kaushik et al, 2015). Cardiac-muscle-specific Vinc overexpression increases fractional shortening and regulates mitochondrial respiration and glucose metabolism, both of which improve cardiac function in the aging fly (Kaushik et al, 2015;Sessions et al, 2018). These data suggest that regulation of VCL expression or function may be a therapeutic target to improve cardiac function in heart failure patients.…”
Section: Discussionmentioning
confidence: 97%
“…It was reported that increased Vinculin (Vinc) expression in Drosophila cardiac muscle cells improves cardiac function and extends lifespan (Kaushik et al, 2015). Cardiac-muscle-specific Vinc overexpression increases fractional shortening and regulates mitochondrial respiration and glucose metabolism, both of which improve cardiac function in the aging fly (Kaushik et al, 2015;Sessions et al, 2018). These data suggest that regulation of VCL expression or function may be a therapeutic target to improve cardiac function in heart failure patients.…”
Section: Discussionmentioning
confidence: 97%
“…This study suggested that cardiomyocytes are sensitive to N-cadherin mediated mechanical signaling and possibly also cell-cell mechanical signaling through the intercalated discs. Other studies have suggested that the loss of intercalated disks plays a role in age-related loss of cardiac function and that reinforcement of the intercalated disks may help preserve cardiac function (Kaushik et al, 2015; Sessions et al, 2018).…”
Section: Current Understanding Of Cardiac Mechanobiologymentioning
confidence: 99%